Swimming practice and scapular kinematics, scapulothoracic muscle activity, and the pressure-pain threshold in young swimmers - Habechian, F. A. P.; Lozana, A. L.; Cools, A,. M.; Camargo, P. R. (Journal of Athletic Training, 2018)
Context Whereas alterations in scapular kinematics, scapulothoracic muscle activity, and pain sensitivity have been described in adult swimmers, no researchers have examined these outcomes in young swimmers.